Granulomatous Bronchiolitis with Necrobiotic Pulmonary Nodules in Chrohn's Disease. (1st November 2004) - Freeman, Hugh J; Davis, Jennifer E; Prest, Marcia E; Lawson, Edward J
Abstract : A 37-year-old man with extensive Crohn's disease of the stomach, small and large intestine for almost a decade developed respiratory symptoms and radiological findings suggestive of pneumonia that failed to resolve with antibiotic treatment. Computed tomography scanning of his lungs showed extensive changes with cavitated parenchymal nodules. Histological evaluation of an open lung biopsy showed granulomatous bronchiolitis and pulmonary necrobiosis. Treatment with steroids and immunosuppression resulted in complete resolution of his clinical symptoms of pneumonia and abnormal computed tomography imaging changes. Granulomatous bronchiolitis and necrobiotic nodules may be a manifestation of Crohn's disease in the absence of microbial agents, including mycobacteria or fungal agents. While a multiplicity of complex pulmonary changes may occur in Crohn's disease, their clinical recognition and precise pathological definition may be particularly important if treatment with a biological agent, such as infliximab, is being considered.